ESOPHAGOANASTOMOSIS COMPLICATIONS IN CHILDREN WITH ATRESIA OF THE PILLOUS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
According to a large number of authors from the CIS countries and foreign countries on the treatment of esophageal atresia in young children, despite a number of achievements, many problems in this regard, as well as problems associated with technical aspects, have not been resolved, and mortality in this pathology is 40- 60%. This guideline describes balloon tamponade of the cardia of the stomach and an improved method of applying esophagoanastomosis with a 180° rotation of the esophagus around its axis and suturing the anterior wall of the esophagus in young children diagnosed with esophageal atresia. The proposed tactical and technical approaches have made it possible to reduce the frequency of early postoperative complications and mortality associated with the operation, improve the quality of life of young children. The manual is intended for pediatric surgeons of neonatal surgery departments of specialized regional children's medical institutions.